Gene activation properties of a mouse DNA sequence isolated by expression selection. - von Hoyningen-Huene, V (1986)
The MES-1 element was previously isolated from restricted total mouse cellular DNA by "expression selection"--the ability to reactivate expression of a test gene devoid of its 5' enhancer sequences. Mes-1 has been tested in long-term transformation and short-term CAT expression assays. In both assays MES-1 is active independent of orientation and at a distance when placed 5' to the test gene. The element is active with heterologous promoters and functions efficiently in both rat and mouse cells. MES-1 activates expression by increasing transcription from the test gene's own start (cap) site. Thus the expression selection technique can be used for the isolation of DNA sequences with enhancer-like properties from total cellular DNA.